2018
DOI: 10.1038/s41598-018-30432-7
|View full text |Cite
|
Sign up to set email alerts
|

Water makes glass elastically stiffer under high-pressure

Abstract: Because of its potentially broad industrial applications, a new synthesis of elastically stiffer and stronger glass has been a long standing interest in material science. Various chemical composition and synthesis condition have so far been extensively tested to meet this requirement. Since hydration of matter, in general, significantly reduces its stiffness, it has long been believed that an anhydrous condition has to be strictly complied in synthesis processes. Here we report elastic wave velocities of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Stress analysis using XRD results yielded moderate and nearly constant uniaxial strain component St of ∼0.06 regardless of experimental pressure conditions (Murakami, 2018; Singh, 1993; Singh & Takemura, 2001), see Text S1 and Figure S1 in Supporting Information S1 for more details. In the absence of single crystal elasticity, it is not possible to directly calculate uniaxial stress components, but based on the straight diffraction line in unrolled diffraction pattern (Figure 2b) this effect is likely relatively small.…”
Section: Resultsmentioning
confidence: 99%
“…Stress analysis using XRD results yielded moderate and nearly constant uniaxial strain component St of ∼0.06 regardless of experimental pressure conditions (Murakami, 2018; Singh, 1993; Singh & Takemura, 2001), see Text S1 and Figure S1 in Supporting Information S1 for more details. In the absence of single crystal elasticity, it is not possible to directly calculate uniaxial stress components, but based on the straight diffraction line in unrolled diffraction pattern (Figure 2b) this effect is likely relatively small.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies using in situ high‐pressure Brillouin scattering spectroscopy on various silicate glasses including SiO 2 , Al‐bearing SiO 2 , hydrous SiO 2 , MgSiO 3 , and Fe‐bearing MgSiO 3 glasses (Mashino et al., 2022; Murakami, 2018; Murakami & Bass, 2010, 2011; Ohira et al., 2016) have suggested that the trend changes in the acoustic velocity profile of silicate glasses as a function of pressure could primarily synchronize with the change in the Si‐O CN (Sato & Funamori, 2008). This interpretation is in fact in good agreement with the theoretical studies (Brazhkin et al., 2011; Karki et al., 2007; Zeidler et al., 2014) and also the recent experimental works on SiO 2 glass obtained up to pressures of ∼200 GPa (Kono et al., 2020; Murakami et al., 2019; Prescher et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, most of those previous high‐pressure Brillouin studies have observed a trend change in the acoustic velocity profile above ∼100 GPa. Based on the criterion mentioned above, it has been suggested that the trend change in the acoustic velocity of silicate glasses with pressure so far observed above ∼100 GPa corresponds to the Si‐O CN changes from 6 to 6 + (Mashino et al., 2022; Murakami, 2018; Murakami & Bass, 2010, 2011; Ohira et al., 2016). The emergence of this ultrahigh‐pressure densification process involved in the higher CN above 6 is also supported by the recent high‐pressure experimental and theoretical works on GeO 2 glass (Brazhkin et al., 2011; Kono et al., 2016; Petitgirard et al., 2019) considered as a promising low‐pressure analog material to SiO 2 glass.…”
Section: Discussionmentioning
confidence: 99%
“…Saha et al [83] applied a pressure of 155 GPa to investigate silicate glasses, and a comparison of their results with those of Mashino et al [84][85][86] showed that the transverse acoustic velocity distribution of (Fe, Al)-silicate glasses became steeper above 98 GPa and eventually became comparable to that of pure MgSiO 3 glasses above 125 GPa, as shown in Figure 12. Thus, the doping of Al into MgSiO 3 glass containing Fe 2þ can significantly increase the elastic hardness of the glass, thereby densifying it at pressures above 100 GPa.…”
Section: Acoustic Performance Measurementmentioning
confidence: 99%